Racial structure of Himalayan Mahseer,Tor putitora (Hamilton) in the river Ganga between Rishikesh and Hardwar - Bhatt, J P; Nautiyal, P; Singh, H R (The Indian Journal of Animal Sciences, 2012)
Study on the racial strucutre of Tor putitora (Hamilton) was conducted in the foothill section of the river Ganga,Correlation cofficient (r)-was Â was significant at P